2022
DOI: 10.3389/fpsyt.2021.780095
|View full text |Cite
|
Sign up to set email alerts
|

A Randomized Controlled Trial on the Effects of a 12-Week High- vs. Low-Intensity Exercise Intervention on Hippocampal Structure and Function in Healthy, Young Adults

Abstract: Physical exercise affects hippocampal structure and function, but the underlying neural mechanisms and the effects of exercise intensity remain incompletely understood. Therefore, we undertook a comprehensive, multi-modal 3T and 7T MRI randomized controlled trial (Netherlands Trial Register - NL5847) in which we randomized 52 young, non-athletic volunteers to a 12-week low- or high-intensity exercise program. Using state-of-the-art methods, we investigated changes in hippocampal volume, as well as changes in v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 115 publications
2
12
0
Order By: Relevance
“…Interestingly, post-exercise hippocampal blood flow never increased above baseline levels in individuals with high perfusion ( Figure 3 ). As we only tested a single type of exercise, it is possible that a different type of exercise stimulus, for example high intensity interval training, may elicit more robust vascular and neural plasticity in these individuals (Boyne et al, 2019; Kaiser et al, 2022; Neva et al, 2022; Weston et al, 2022). The present results provide preliminary evidence for the use of baseline cerebrovascular perfusion as a predictive biomarker for brain health benefit from exercise in aging populations.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, post-exercise hippocampal blood flow never increased above baseline levels in individuals with high perfusion ( Figure 3 ). As we only tested a single type of exercise, it is possible that a different type of exercise stimulus, for example high intensity interval training, may elicit more robust vascular and neural plasticity in these individuals (Boyne et al, 2019; Kaiser et al, 2022; Neva et al, 2022; Weston et al, 2022). The present results provide preliminary evidence for the use of baseline cerebrovascular perfusion as a predictive biomarker for brain health benefit from exercise in aging populations.…”
Section: Discussionmentioning
confidence: 99%
“…Two studies found increases in either whole-brain CBF (Espeland et al, 2018) or gray-matter CBF (Robertson et al, 2017), while in eight other studies no differences were observed (Anazodo et al, 2016;Chapman et al, 2013Chapman et al, , 2016Chapman et al, , 2017Kaiser et al, 2021;Kleinloog et al, 2019;Maass et al, 2015;Moore et al, 2015;Steventon et al, 2021;van der Kleij et al, 2018). Studies that focused on differences in blood flow in brain lobes observed an increased CBF in the limbic (Espeland et al, 2018), occipital (Espeland et al, 2018), medial temporal (Moore et al, 2015), and parietal lobe (Robertson et al, 2017).…”
Section: Magnetic Resonance Imagingmentioning
confidence: 97%
“…Finally, 45 original intervention studies were identified, of which 16 used MRI (10 of these studies used arterial spin labeling, two studies used gadolinium as a contrast agent, and one study used PET), 20 transcranial Doppler ultrasound, and eight NIRS. Twenty-six RCTs were included (MRI: n = 10 [ Chapman et al, 2013;Espeland et al, 2018;Kaiser et al, 2021;Kaufman et al, 2021;Kleinloog et al, 2019;Maass et al, 2015;Maffei et al, 2017;Moore et al, 2015;Small et al, 2006;van der Kleij et al, 2018]; transcranial Doppler ultrasound: n = 12 [Akazawa et al, 2012;Bailey, Cable, Aziz, Atkinson, et al, 2016;Cho & Roh, 2019;Green et al, 2021;Hata et al, 1998;Heli et al, 2013;Ivey et al, 2011;Lee et al, 2021;Miller et al, 2022;Northey et al, 2019;Thomas et al, 2021;Tomoto, Liu, et al, 2021]; and NIRS: n = 4 [Fu et al, 2013;Hamasaki et al, 2019;Tsai et al, 2016;Wang et al, 2010]) that involved a control group, which performed no exercise or performed activities not affecting fitness levels (e.g., yoga or stretching). The remaining 18 studies (MRI: n = 6 [Alfini et al, 2019;Anazodo et al, 2016;Burdette et al, 2010;Pereira et al, 2007;Robertson et al, 2017;Steventon et al, 2021]; transcranial Doppler ultrasound: n = 8 [Akazawa et al, 2018;Bailey, Cable, Miller, et al, 2016;Drapeau et al, 2019;…”
Section: Study Characteristicsmentioning
confidence: 99%
See 2 more Smart Citations